Nov zanimiv amonit iz prodišča ob Sori - Križnar, Matija (Loški razgledi, 2015)
An interesting new Triassic ammonite was found in a gravel bank of the River Sora, between Godešič and Reteče. Based on the shape of the internal ammonite mould and some other information, the specimen dates from the Upper Triassic and is similar to cephalopods of the Arcestidae family. This specimen is one of the most beautiful fossils from secondary sites in the vicinity of Škofja Loka.
Keywords: amoniti; paleontologija; Slovenija; Sora; trias